1994
DOI: 10.1099/0022-1317-75-5-1043
|View full text |Cite
|
Sign up to set email alerts
|

Role of N-linked Oligosaccharide Chains in the Processing and Antigenicity of Measles Virus Haemagglutinin Protein

Abstract: The effects of N-linked oligosaccharides on the haemagglutinin (H) protein of measles virus (MV) were assessed with respect to the processing and antigenicity of the molecule. The functional glycosylation sites on the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
62
1

Year Published

1994
1994
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(64 citation statements)
references
References 38 publications
1
62
1
Order By: Relevance
“…1 A and 2), defining their orientation and possibly excluding spatial proximity of the N215-linked sugars. Previous studies (18) showed that two other potential N-linked sites (N168 and N187) are also sugar-modified, although those sugars were not visible in our crystal. Thus, wide areas of MV-H appear to be covered with N-linked sugars (SI Fig.…”
Section: Resultscontrasting
confidence: 43%
“…1 A and 2), defining their orientation and possibly excluding spatial proximity of the N215-linked sugars. Previous studies (18) showed that two other potential N-linked sites (N168 and N187) are also sugar-modified, although those sugars were not visible in our crystal. Thus, wide areas of MV-H appear to be covered with N-linked sugars (SI Fig.…”
Section: Resultscontrasting
confidence: 43%
“…MV F protein function has more stringent requirements for glycosylation on all potential sites than H protein function: when tested in the same experimental system single-or double-site glycosylation mutants of the MV H proteins (Hu et al, 1994a) retained fusion-helper function, whereas only one of the single-site F protein glycosylation mutants retained fusion function. Indeed, the F and H proteins of MV, as with those of other paramyxoviruses have quite distinct properties regarding their intracellular processing (Mottet et al, 1986;Morrison & Portner, 1991 ;Hu et al, 1994a, b).…”
mentioning
confidence: 99%
“…To evaluate the possible contribution of N-linked oligosaccharide side chains on the H and F proteins to cell fusion, the F glycosylation mutants generated in this study and the previously produced H glycosylation mutants (Hu et al, 1994a) were co-expressed in HeLa T4 cells. All possible combinations between the F and H glycosylation mutants were used to cotransfect HeLa T4 cells and the capacity to cause cell fusion was determined under conditions described in Cattaneo & Rose (1993).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, assessment of the role of individual sugar side chains can be done by utilizing site-directed mutagenesis of the consensus sequence (Asn-X-Thr/Ser) for oligosaccharide attachment. These studies reveal that role of the N-linked oligosaccharides on glycoprotein maturation varies from one glycoprotein to the other [2,7,10,12]. …”
mentioning
confidence: 99%